KEGIATAN KEPRAMUKAAN SEBAGAI SARANA MENUMBUHKAN KREATIVITAS PESERTA DIDIK DI MTS 2 DARUL AITAM MENGKURU - Iza Syahroni; Erni Munastiwi (Universitas Singaperbangsa Karawang, 2021)
Scout is an outdoor activity. With the existence scout at schools, it is hoped that it can help students to increase their creativity, so that they can produce quality students who can compete in. This study aimed to (1) how the scouting activities as a place to increase the creativity of students in MTS 2 Darul Aitam Mengkuru. (2) what is the strategy to develop the creativity of students through scouting activities at MTS 2 Darul Aitam Mengkuru. By using a qualitative approach with a case study approach. The data sources consisted of 8 scout members and 4 trainers, school principals, and scout coaches. The data collection techniques used are interviews, observation, and documentation. The data analysis used is an interactive method. The results of the study found that the scouting activities carried out to develop and realize the creativity of MTS 2 Darul Aitam Mengkuru students included several activities including: rigging, ciphering, work cubes and LKBB creations. Then, the strategy to increase the creativity the students At MTS 2 Darul Aitam Mengkuru are create a fun and fun learning atmosphere, become a coach as well as a friend, students are given freedom in creating, and with regular guidance